2021
DOI: 10.1108/ijlls-03-2021-0026
|View full text |Cite
|
Sign up to set email alerts
|

Exploring teacher learning process in Chinese lesson study: a case of representing fractions on a number line

Abstract: PurposeThis paper presented the learning process of a group of primary mathematics teachers who participated in two iterations of lesson design, enactment and reflection in a Chinese Lesson Study.Design/methodology/approachAn expansive learning theory was employed to examine the teachers’ learning process in lesson study (LS) on representing fractions on a number line. The evolution of a germ cell was utilized to feature the transformation of the object of activity from abstract to concrete through resolving c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 21 publications
(44 reference statements)
0
4
0
Order By: Relevance
“…In terms of working mode, LS consists of four stages: (a) study, where learning objects are set for students based on their learning status; (b) plan, where the community collaborates to design a research lesson to achieve the learning objects; (c) teach, where community members teach this lesson in the classroom as well as record the lesson; and (d) reflect, where the research lesson is reflected on and improved based on the classroom records [8]. Although some researchers nuanced these stages, a consensus has been reached concerning the critical characteristics of LS, including the emphasis on collaboration among groups [15] and evidence-based lesson analysis [24]. Empirical studies have shown that LS can enhance teachers' understanding of teaching and learning, improve their ability to design teaching, and facilitate their practice of curriculum ideas [9,[25][26][27][28], as evidenced by the fact that its significance in promoting teachers' sustainable professional development has been extensively recognized at the international level.…”
Section: Lsmentioning
confidence: 99%
See 3 more Smart Citations
“…In terms of working mode, LS consists of four stages: (a) study, where learning objects are set for students based on their learning status; (b) plan, where the community collaborates to design a research lesson to achieve the learning objects; (c) teach, where community members teach this lesson in the classroom as well as record the lesson; and (d) reflect, where the research lesson is reflected on and improved based on the classroom records [8]. Although some researchers nuanced these stages, a consensus has been reached concerning the critical characteristics of LS, including the emphasis on collaboration among groups [15] and evidence-based lesson analysis [24]. Empirical studies have shown that LS can enhance teachers' understanding of teaching and learning, improve their ability to design teaching, and facilitate their practice of curriculum ideas [9,[25][26][27][28], as evidenced by the fact that its significance in promoting teachers' sustainable professional development has been extensively recognized at the international level.…”
Section: Lsmentioning
confidence: 99%
“…Along with rapidly iterating curriculum standards and emerging pedagogical ideas, coupled with closer interactions, discussions, and seminars between university researchers and frontline teachers, various LSs are taking place in regular teaching in Chinese elementary and secondary schools (e.g., [15,29]. Chinese pedagogical research activities are dedicated to producing high-quality, exquisite lessons (jingpin lessons, in Chinese), and thus LS often involves an iterative cycle of study, design, formulation, reflection, and refinement [11,29] and usually requires intellectual support from academic and practical experts to build such exquisite lessons [13].…”
Section: Lsmentioning
confidence: 99%
See 2 more Smart Citations